A violência familiar contra crianças e adolescentes e a intervenção das equipes de saúde da família do município de Ponta Grossa. - Sonego, Cristiane (2006)
The problem of violence practiced in the family environment presents itself as a reality which is lived by a large number of children and adolescents nowadays, bringing about, together with the abusive use of parents’ authority, consequences to the children’s health. Facing such a problem, this research aimed at raising the discussion on home violence against children and adolescents and the fight against it in the Health System, through the Family Health Program in the city of Ponta Grossa. The general objective of this work is to discuss the phenomenon of home violence and analyze the interference of professionals in the Family Health Teams in this town. In order to achieve this objective, within a proposal of quantitative and qualitative research, an ample literature review was carried out to provide the basis and approach the reality directly, as well as to support the analysis of data collected. A questionnaire with open and closed questions and a semi-structured interview were used. The work is divided into four chapters. In the first chapter, the violence in social relations, including home violence against children and adolescents, is approached, considering its historical aspects and the legal constituted basis for its combat. The second chapter discusses home violence against children and adolescents, its concepts, manifestations, characteristics and its expression in the current social context. The relation between violence fighting and the Brazilian Health Policy as well as the role of the Family Health Program intervention on the problem are surveyed. Chapter four deals with the data analysis, the fight against home violence against children and adolescents by the Family Health Program in Ponta Grossa - PR. The research tried to contribute to the widening of the discussion about home violence against children and adolescents, pointing out the importance of the Family Health Program professionals’ interference. As final considerations we present suggestions to optimize these teams work towards the problem.